P09 Serum neurofilament light chain levels are an independent predictor of neurodevelopmental outcome in preterm infants. Issue 6 (17th May 2019) - Hauck, A; Goeral, K; Atkinson, A; Fuiko, R; Leeb, C; Michalak, Z; Klebermass, K; van den Anker, J; Berger, A; Kuhle, J; Olischar, M; Wellmann, S
Abstract : Background and Purpose: Serum neurofilament light chain (sNfL) has recently emerged as a promising biomarker reflecting structural neuro-axonal damage in different neurological diseases. Our study aimed at assessing whether sNfL can predict the functional outcome in preterm infants who suffered from neonatal haemorrhagic brain injury. Methods: In this prospective observational study, we used an ultrasensitive single-molecule array assay to measure serum and cerebrospinal fluid (CSF) concentrations of NfL in preterm infants diagnosed with intraventricular haemorrhage (IVH) in the first few days of life. We determined the temporal profile of serum and CSF NfL levels from first diagnosis of IVH until term equivalent age, their association with cerebral imaging markers, and with clinical and functional outcome until 2 years of age assessed by Bayley Scales of Infant Development. We fitted univariable and multivariable logistic regression models to determine risk factors for low motor and cognitive development. Longitudinal mixed effects models modelled NfL levels using cubic spline smoothers to track the trajectory over time. Results: The study included 48 infants born with less than 32 weeks of gestation. At the time point of IVH diagnosis, NfL median levels were 271.9 pg/mL (IQR 151.2–389.7), and strongly decreased until term equivalent age to 15.7 pg/mL (IQR 11.1–32.2). CSF values were 113-fold higher (IQR 40–211) than corresponding serum values. Additional cerebral infarction (n=23) but not post-haemorrhagic hydrocephalus with permanent external ventricular drainage (n=29) or other diseases independently determined sNfL levels. In multivariate logistic regression models, the only significant predictor of poor motor outcome at 2 years or death was sNfL level (p=0.02).There was a clear difference between the NfL trajectory for those with poor motor outcome at 1 year. Conclusions: This study shows that early sNfL is an independent prognostic biomarker for motor functional outcome in preterm infants after IVH. Disclosure(s): Nothing to disclose